A good balance between strength and ductility in Mg–Zn–Mn-Gd alloy. (May 2021) - Zhao, Yang; Zhang, Dingfei; Xu, Junyao; Zhong, Shiyu; Jiang, Bin; Pan, Fusheng
Abstract: Microstructure evolution, dynamic recrystallization (DRX) behavior and mechanical properties of Mg–6Zn–1Mn- x Gd alloys ( x = 0, 0.2, 1.0 and 3.0 wt%) were investigated. The results showed that the phase components of as-cast Mg–6Zn–1Mn alloy were comprised of Mg7 Zn3, α-Mn and α-Mg, while Mg3 Zn6 Gd (I phase) and Mg3 Zn3 Gd2 (W phase) were detected with the addition of Gd. Gd addition led to finer recrystallized grains, and it retarded DRX process due to the obstruction of nano-scale particles to grain boundaries. All as-extruded alloys exhibited typical basal texture, but Gd addition resulted in a low pole density of basal texture. Mg–6Zn–1Mn-3.0Gd alloy (ZMG613) exhibited a good balance between the strength and ductility with an ultimate tensile strength (UTS) of 354 MPa, yield strength (YS) of 306 MPa and elongation (EL) of 15.7%. Fine grain strengthening, second phase strengthening and dislocation strengthening were mostly contributed to the achievement of high strength. And the excellent ductility was mainly ascribed to the finer grains, weak basal texture, nano-scale I phase and non-basal slip activation. Highlights: A good balance between strength and ductility is achieved in Mg–Zn–Mn-Gd alloy. Gd addition can significantly refine grains, but it has little influence on DRXed fractions. Fine grains, nano particles, weak texture and activation of non basal slip lead to the balanced properties.